DETERMINAN INVESTMENT OPPORTUNITY SET DAN FREE CASH FLOW SEBAGAI PEMODERASI - Kurniawan, Elan (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
The purpose of this study is to examine sales growth, earning growth, asset growth influence the Investment opportunity set with free cash flow as a moderating retail trade company listed on the Indonesia Stock Exchange. This type of research is quantitative research, with the population used are all retail trading companies listed on the Indonesia Stock Exchange during the year ie between 2014 and 2017 as many as 11 companies. The sampling technique using purposive sampling method with data analysis techniques, namely multiple linear regression equations with hypothesis testing using SPSS. Based on the results of hypothesis testing, it shows that the sales growth variable has a significant positive effect on the Investment opportunity set but the profit growth and asset growth variable has no significant effect on the Investment opportunity set while the free cash flow moderates significantly positive on the sales growth of the Investment opportunity set.